Pengaruh Whistleblowing System, Kompetensi, Good Corporate Governance, dan Efektivitas Pengendalian Internal terhadap Pencegahan Kecurangan - Utama, Kadek Deni Sandira; Astawa, I Gede Putu Banu (Vokasi : Jurnal Riset Akuntansi, 2021)
Abstract This study aims to obtain empirical evidence regarding the effect of the whistleblowing system, human resource competence, good corporate governance, and the effectiveness of internal controls on fraud prevention in the management of LPD funds in Buleleng Regency. This research is a quantitative research with 75 respondents. The method of determining the sample using purposive sampling technique. The data used are primary data obtained through a questionnaire and measured using a Likert scale. The data analysis techniques used are Validity Test, Reliability Test, Classic Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test, and t-test with the help of SPSS 26.0 for Windows. The results show that the whistleblowing system, human resource competence, good corporate governance, and the effectiveness of internal control have a positive and significant effect on preventing fraud in the management of LPD funds in Buleleng Regency. Keywords : fraud prevention, whistleblowing system, human resource competence, good corporate governance, and effectiveness of internal control